2022
DOI: 10.1109/tgrs.2021.3125567
|View full text |Cite
|
Sign up to set email alerts
|

The Φ-Sat-1 Mission: The First On-Board Deep Neural Network Demonstrator for Satellite Earth Observation

Abstract: Artificial intelligence (AI) is paving the way for a new era of algorithms focusing directly on the information contained in the data, autonomously extracting relevant features for a given application. While the initial paradigm was to have these applications run by a server hosted processor, recent advances in microelectronics provide hardware accelerators with an efficient ratio between computation and energy consumption, enabling the implementation of AI algorithms "at the edge." In this way only the meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…On-orbit processing is an emerging field in the setting of deep-learning based earth observation problems. Initial implementations, such as the CloudScout neural network on-board ESA's Φ-Sat 1, have yielded promising results [6,15]. Implementing neural networks on-orbit provides several advantages to small satellite operations, including a heavily reduced communications bandwidth [16], improved scalability, and the capability for each satellite to be tuned and re-trained with its captured raw data [17], tailoring an algorithm to a specific end device.…”
Section: On-orbit Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…On-orbit processing is an emerging field in the setting of deep-learning based earth observation problems. Initial implementations, such as the CloudScout neural network on-board ESA's Φ-Sat 1, have yielded promising results [6,15]. Implementing neural networks on-orbit provides several advantages to small satellite operations, including a heavily reduced communications bandwidth [16], improved scalability, and the capability for each satellite to be tuned and re-trained with its captured raw data [17], tailoring an algorithm to a specific end device.…”
Section: On-orbit Processingmentioning
confidence: 99%
“…Unfortunately, due to a variety of factors relating to the resolution and source platforms that the datasets were built from, these datasets were not suitable for use in this work. This is an issue seen in other papers in the field [4,6], which has lead to authors creating their own novel datasets for algorithms; an approach which can also be seen implemented here.…”
Section: A Dataset Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, MicroSats and NanoSats cannot adopt expensive, large-scale FPGAs as computation devices, which means DSPs and other hardware resources are precious to them. Meanwhile, spaceborne remote sensing platforms not only perform CNN-based image processing, but also perform image preprocessing, such as radiation correction and image dehazing, to improve the performance of CNN-based image processing [24]. Some FPGA-based studies showed that image preprocessing requires a lot of hardware resources to implement [25,26].…”
Section: Introductionmentioning
confidence: 99%